PERBEDAAN KEMAMPUAN CANGKANG KERANG, CANGKANG KEPITING DENGAN CANGKANG UDANG SEBAGAI KOAGULAN ALAMI DALAM PENJERNIHAN AIR SUMUR DI DESA TANJUNG IBUS KECAMATAN SECANGGANG KABUPATEN LANGKAT - Sailent Rizki Simaremare; surya dharma; nurmaini * (Lingkungan dan Kesehatan Kerja, 2014)
Water is a basic need for human life on this earth. Human life needs water to support their daily life. The water need varies depending on climatic conditions, living standards, and culture of the people. People in the village of Tanjung Ibus, District Secanggang, majority of the people using wells as the main source of water supply. The condition of wells water and bore dug wells in the village physically looks turbid and brackish and some people do not use a water filter to resolve the issue.This study aimed to find out the difference of ability between shell clams, crab shells with shrimp shells as a natural coagulant in water wells purification in the village of Tanjung Ibus District Secanggang.The design of this study was quasi-experiment . The research was held in the Laboratory of Tirtanadi Sunggal and in the village of Tanjung Ibus District Secanggang Langkat district. Analysis of the data was using one-way ANOVA statistical test with α = 0.05% Based on statistical test, the highest average reduction of water turbidity was shell calsium carbonate as 95,28 and the lowest was 91,58% in control. As well as the pH decreased by 28,57% from 7.0 to 5.0 on the addition of coagulant. Based on One-Way ANOVA test the turbidity in well water obtained that there isn’t a significant difference among the ability of calcium carbonate shells, shell crab chitosan and shell shrimp chitosan as  natural coagulants in water purification , p value = 0.05. For that it is needed the role of the society and the government in improving and improvement the clean water for the society so that it is obtained water that appropriate to health requirements.